12 Years Later: Reflections on the Growth of the UN Global Compact. (March 2013) - Kell, Georg
The United Nations (UN) Global Compact's journey over the last 12 years can be summarized as building and integrating UN issues into the global corporate responsibility movement. This summary begs the question as to how a policy speech developed for the UN secretary-general has evolved into an innovative public–private partnership initiative. This article argues that the following four factors contributed to creating enabling ingredients for the UN Global Compact's growth: continued relevance of the initiative's underlying idea, sustained institutional leadership support, governmental support (political back-up), and operational viability . Based on the author's personal experience with the initiative from its inception, the article highlights what is required for an initial idea to be developed into a vibrant operational entity in the context of a multilateral organization. Specially, the article reflects on how the aforementioned four attributes have interacted with each other throughout the last 12 years.